Digital Innovations for Managing Climate Risks - Koo, Jawoo (International Food Policy Research Institute, 2022)
The lead of CGIAR Research Initiative on Digital Innovation, Jawoo Koo at IFPRI, was invited to give a keynote presentation at the Asia-Pacific Economic Cooperation (APEC) webinar on “Digitalization and Innovation of APEC Food System" on 1 December 2022.